Review and ranking the private insurance companies in Iran based on TOPSIS model - Asadi, Leila; Esmaeilzadeh Moghri, Ali (International Journal of Accounting and Economics Studies, 2016)
Insurance companies are the most important economic institutions in each country and they support other economic entities. Their proper performance play an important role in the booming the economy. Insurance companies to achieve effective and strong performance should be familiar with performance of competitors and themselves and according to their information take necessary measures. For this purpose, the current study aims to rank the private insurance companies. In this regard, financial and non-financial indicators as well as performance index for 17 private insurance companies are extracted over 4 years (2011 to 2014) based on their financial statements. The weight of each index was determined using the Shannon entropy. Then, insurance companies were ranked using TOPSIS. The results showed that based on financial indicators, Arman insurance company in 2011 and 2012 had the optimal performance from the standpoint of the criteria (1st). In the years, 2013 and 2014 Kosar insurance Company and Mihan insurance companies were at the 1st place. In addition, Alborz insurance Company had a good performance in terms of performance indexes in 2011 and 2013, (1st). In the years 2012 and 2014, Parsian and Pasargad Insurance Companies ranked 1st. Based on non-financial indicators, Asia insurance company in the period under review (2011 to 2014) ranked in the first place.